PENGARUH TREN MENJADI CONTENT CREATOR TERHADAP ANGKATAN KERJA GENERASI Z - Nalya Puspa Harlisa; Mirna Nur Aliya Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
The labor force is the productive-age population that is doing a job, has a job or is looking for a job. The focus is on people who are looking for work, indirectly they are still unemployed and waiting for work. Generation Z itself is one of the contributors to the labor force in Indonesia. Born in an era where technology is increasingly developing, Generation Z has a creative mind that can create new jobs in this digital era such as Content Creator. The purpose of this study is to find out the generation Z workforce who are interested in content creator jobs, and the effect of becoming a content creator on the generation Z workforce. The content creator trend as a job in this digital era affects the generation Z workforce and can reduce the existing unemployment rate. In addition, it can develop the talents and interests possessed by generation Z because they have creativity so that they can hone the skills they have. The trend of content creators as a job in this digital era affects the generation Z workforce and can reduce the existing unemployment rate. In addition, it can develop the talents and interests possessed by generation Z because they have creativity so that they can sharpen the skills they have.